2012
DOI: 10.11113/jt.v35.594
|View full text |Cite
|
Sign up to set email alerts
|

Intelligent Adaptive Active Force Control of a Robotic Arm with Embedded Iterative Learning Algorithms

Abstract: Kawalan jitu dan lasak bagi satu sistem lengan robot atau pengolah adalah amat penting terutama sekali jika sistem mengalami pelbagai bentuk bebanan dan keadaan pengendalian. Kertas kerja ini memaparkan satu kaedah baru dan lasak untuk mengawal lengan robot menggunakan teknik pembelajaran secara berlelaran yang dimuatkan dalam strategi kawalan daya aktif. Sebanyak dua algoritma pembelajaran utama digunakan dalam kajian – yang pertama digunakan untuk menala gandaan pengawal secara automatik manakala yang satu l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
36
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1
1

Relationship

5
3

Authors

Journals

citations
Cited by 19 publications
(41 citation statements)
references
References 4 publications
0
36
0
Order By: Relevance
“…The results of these studies revealed the AFC strategy is more effective in attenuating the amplitude of undesired vibrations of the system. Since the most crucial computational part in AFC is the approximation of the estimated mass or moment of inertia of any dynamical system, the use of artificial intelligence (AI) method such as artificial neural network (ANN) and iterative learning (IL) to determine this parameter has been initiated by Mailah (1998 (Mailah, 1998). Also, to the author knowledge, there is no available literature on the application of AFC approach to control the unwanted vibration of a spray boom directly.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The results of these studies revealed the AFC strategy is more effective in attenuating the amplitude of undesired vibrations of the system. Since the most crucial computational part in AFC is the approximation of the estimated mass or moment of inertia of any dynamical system, the use of artificial intelligence (AI) method such as artificial neural network (ANN) and iterative learning (IL) to determine this parameter has been initiated by Mailah (1998 (Mailah, 1998). Also, to the author knowledge, there is no available literature on the application of AFC approach to control the unwanted vibration of a spray boom directly.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the active control suspensions are still less applied while undesired boom oscillations have been characterized as a great restriction for chemical distribution uniformity (Anthonis et al, 2005). Additionally, conventional control method which is simple and relatively stable could just guarantee satisfactory performance at a very low speed operation (Mailah, 1998).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This method turned out to be very robust and effective in controlling a robot arm. Later on other researchers successfully implemented this procedure for a robot arm by combining artificial intelligent (Mailah, 1998;Mailah & Rahim, 2000), as well as controlling pneumatic actuators (Mailah et al, 2009). The AFC method was very capable and successful for decreasing friction induced vibrations (Hashemi-Dehkordi et al, 2009a;Hashemi-Dehkordi et al, 2010;Hashemi-Dehkordi et al, 2009b;Hashemi-Dehkordi et al, 2012;Hashemi-Dehkordi et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The AFC method was first proposed by Hewit and Burdess (1981), and it was noticed that the AFC method was very robust and operative in controlling a robot arm. Afterward, other researchers implemented the AFC method very successfully for a robot arm by taking into consideration artificial intelligence techniques (Mailah, 1998;Mailah & Rahim, 2000), in addition to controlling actuators of pneumatic types (Mailah et al, 2009). The AFC method was successful for reducing friction induced vibrations (Hashemi-Dehkordi et al, 2009a;HashemiDehkordi et al, 2009b;Hashemi-Dehkordi et al, 2010;Hashemi-Dehkordi et al, 2012;HashemiDehkordi et al, 2014).…”
Section: Introductionmentioning
confidence: 99%